Performance and body composition of pigs reared under tropical conditions receiving two crude protein levels: conventional and precision feeding - Santos, L. S. [UNESP]; Campos, P. H. R. F.; Pomar, C.; Hauschild, L. [UNESP]; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
In this study the performance and the body composition of pigs under individual precision feeding (IPF) or conventional (CON) feeding systems, and fed high (HCP) or low (LCP) crude protein content diets under tropical conditions were evaluated. During 56 days, 60 castrated male pigs (39.6 +/- 1.29 kg of BW) were assigned to one of the four experimental treatments distributed in a 2x2 factorial design consisted of two feeding systems (CON and IPF), and two CP formulation (LCP and HCP). Pigs in the CON group received 1.02 and 0.85% of SID Lys during phases I (0-28 d) and II (29-56 d), respectively. IPF pigs received daily a personalized diet. The body protein and body lipid content were accessed using a DXA equipment at days 0, 28 and 56 of experiment. IPF pigs reduced their ADFI when fed a HCP diet during the first and second experimental phase (P<0.07 for FS x CP). Pigs receiving LCP diets showed greater ADG (P<0.01) than pigs fed a HCP diet. The body protein content of pigs fed a LCP during phase I (P=0.08) was greater than in pigs fed the HCP diet. Yet, CON pigs fed a HCP diet showed a compromised feed efficiency compared with CON pigs fed a LCP diet (P<0.07 for FS x CP). Under tropical conditions, the IPF technique is suitable even when HCP diets are used. However, to ensure a greater feed efficiency in CON systems, the use of industrial AA to reduce CP levels is recommended.
Keywords: body lipid; body protein; heat stress; low crude protein; tropical climate